The Fatimids - Jiwa, Shainool. (London ; New York London ; New York)
2 cilt (1. c. [2], 154 s. ; 2. c. vi sayfa, [1] sayfa harita)
Keywords: “The Fatimids were one of most prosperous and influential dynasties of the medieval Muslim world, ruling from 909-1171. At its height, their empire extended from the Atlantic shores of North Africa to the Red Sea. But it was their conquest of Egypt in 969 that marked the inception of a burgeoning Mediterranean empire. This book - the second and final part on the Fatimids - continues the story from their newly founded capital city of Cairo. Drawing on a broad range of primary sources, the book navigates readers through a two-century journey that witnessed the triumphs and trials of the only sustained Shi'i caliphate to rule across the Islamic world. You will follow the empire's expansion, including the proclamation of the Fatimid Caliphate in Baghdad, its mission to reunite Muslims under its own Isma'ili Shi'ite caliphate, and the political and religious reasons that led to its final fall when Saladin invaded their territory. The book introduces the figures who molded the empire - from the Imam-caliphs, viziers and generals, to the scholars, scientists, sailors, textile-workers and remarkable women - bringing this renowned dynasty to life“ --